Interroger l’organisation du travail au regard des marges de manœuvre en conception et en fonctionnement. La rotation est-elle une solution aux TMS ? - Fabien Coutarel; François Daniellou; Bernard Dugué (Perspectives Interdisciplinaires sur le Travail et la Santé)
A participatory ergonomic intervention was conducted to design a station for cutting fattened duck. The methodology implemented, based on project management, allowed the ergonomists to be involved in the design of production tools, in work organization on the production line, in training the operators in the new cutting method, and in the effective presence of nearby support.It is mainly in relation to this intervention, but without having all the results, that we propose to define a theoretical framework in the first part of this paper, as well as a methodological framework so that the overall understanding of prevention of musculoskeletal disorders (MSD) in design can be developed around the concept of margin of maneuver.Then, by examining rotation from the standpoint of the operators’ margins of maneuver, we will attempt to establish some conditions for implementing rotation at a meat cutting station, so that rotation can be an effective solution for MSD prevention, but also for production efficiency.